Development and characterization of ligand-appended liposomes for multiple drug therapy for pulmonary tuberculosis. (February 2013) - Bhardwaj, Ankur; Kumar, Lalit; Narang, R. K.; Murthy, R. S. R.
Abstract Tuberculosis (TB) remains one of the oldest and deadliest diseases in the current scenario. The intracellular organism Mycobacterium tuberculosis, which mainly resides in mononuclear phagocytes, is responsible for tuberculosis in humans. A few therapies are available for the treatment of tuberculosis but they have many hurdles. To overcome these hurdles, a combination of chemotherapeutic agent-loaded vesicular systems have been prepared to overcome tuberculosis. To investigate the role of novel drug delivery systems for the treatment of pulmonary tuberculosis, ligand appended liposomals have been developed. In the present study, drug-loaded, ligand-appended liposomes and their DPI (Dry Powder Inhaler) forms have been prepared and characterized using various in vitro and in vivo parameters. The prepared ligand-appended liposomal formulation showed good entrapment efficiency, prolonged drug release, improved recovery of drugs from the target site, and proved to be more suitable for use as DPI, justifying their potential for improved drug delivery. Thus we tried our best by our project to reduce the national burden of tuberculosis, which is still a global health challenge.